2013
DOI: 10.3389/fpls.2013.00395
|View full text |Cite
|
Sign up to set email alerts
|

The current status of the elemental defense hypothesis in relation to pathogens

Abstract: Metal hyperaccumulating plants are able to accumulate exceptionally high concentrations of metals, such as zinc, nickel, or cadmium, in their aerial tissues. These metals reach concentrations that would be toxic to most other plant species. This trait has evolved multiple times independently in the plant kingdom. Recent studies have provided new insight into the ecological and evolutionary significance of this trait, by showing that some metal hyperaccumulating plants can use high concentrations of accumulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 131 publications
0
50
0
2
Order By: Relevance
“…Previously, we have demonstrated that endophytic bacteria of the zinc hyperaccumulator N. caerulescens show higher zinc tolerance when compared with bacteria pathogenic on related non-accumulator plants [15], an idea supported by other studies of bacteria associated with metal-hyperaccumulating plants [18,19,[38][39][40]. Considered alongside evidence for a role of hyperaccumulated metals in defence of plants such as N. caerulescens against disease [ [13][14][15]41,42], this suggests that local adaptation of pathogens to high-metal concentrations in the rhizosphere and phyllosphere of metal-accumulating plants might drive the evolution of further defensive hyperaccumulation in a form of coevolutionary arms race [15,43].…”
Section: Discussionmentioning
confidence: 81%
“…Previously, we have demonstrated that endophytic bacteria of the zinc hyperaccumulator N. caerulescens show higher zinc tolerance when compared with bacteria pathogenic on related non-accumulator plants [15], an idea supported by other studies of bacteria associated with metal-hyperaccumulating plants [18,19,[38][39][40]. Considered alongside evidence for a role of hyperaccumulated metals in defence of plants such as N. caerulescens against disease [ [13][14][15]41,42], this suggests that local adaptation of pathogens to high-metal concentrations in the rhizosphere and phyllosphere of metal-accumulating plants might drive the evolution of further defensive hyperaccumulation in a form of coevolutionary arms race [15,43].…”
Section: Discussionmentioning
confidence: 81%
“…As part of this adaptation, they not only tolerate exposure to normally lethal concentrations of both metals, but also hyperaccumulate them in their shoots, probably as protection against herbivory and microbial infection (Hoerger et al, 2013). N. caerulescens is the only species that also hyperaccumulates Ni and Pb.…”
Section: Discussionmentioning
confidence: 99%
“…The “joint effect” hypothesis is based on the idea that organic defences increase the defensive effect of metals (Boyd, 2007, 2012b). On this basis, conceptual models have been developed which might explain the evolutionary emergence of the hyperaccumulation trait (Boyd, 2012a,b; Hörger et al, 2013). …”
Section: Discussionmentioning
confidence: 99%